2021
DOI: 10.1007/s40265-021-01498-x
|View full text |Cite
|
Sign up to set email alerts
|

Prior Treatment with Statins is Associated with Improved Outcomes of Patients with COVID-19: Data from the SEMI-COVID-19 Registry

Abstract: Background The impact of statins on COVID-19 outcomes is important given the high prevalence of their use among individuals at risk for severe COVID-19. Our aim is to assess whether patients receiving chronic statin treatment who are hospitalized with COVID-19 have reduced in-hospital mortality if statin therapy is maintained during hospitalization. Methods This work is a cross-sectional, observational, retrospective multicenter study that analyzed 2921 patients who req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 34 publications
0
44
0
3
Order By: Relevance
“…After the removal of duplications and irrelevant literature, 56 full-text articles were assessed for eligibility. A total of 35 studies [ 11 45 ] (32 published studies [ 11 – 24 , 26 29 , 31 35 , 37 – 45 ] and three studies available as a preprint [ 25 , 30 , 36 ]) that corresponded to the inclusion and exclusion criteria were included in the systematic review and meta-analyses (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the removal of duplications and irrelevant literature, 56 full-text articles were assessed for eligibility. A total of 35 studies [ 11 45 ] (32 published studies [ 11 – 24 , 26 29 , 31 35 , 37 – 45 ] and three studies available as a preprint [ 25 , 30 , 36 ]) that corresponded to the inclusion and exclusion criteria were included in the systematic review and meta-analyses (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All the included studies [ 11 45 ] are observational studies, reported as cohort/case–control studies or database reviews. All except seven studies [ 18 , 26 , 29 , 34 , 35 , 38 , 39 ] were based directly on the hospital (or nursing home) medical records, and 12 of the included studies [ 13 , 20 , 22 , 23 , 25 , 31 , 33 , 36 , 41 – 44 ] are single-centered observational studies. These hospital- (or nursing home)-based studies [ 11 17 , 19 – 25 , 27 , 28 , 30 – 34 , 36 , 37 , 40 – 45 ] covered a moderate number of participants per study (median 840.0, interquartile range 286.5–1997.5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies of patients with SARS-CoV-2 infection demonstrated the beneficial effects of statins, significantly reducing mortality rates and disease severity [9][10][11][12] .…”
Section: Effect Of Statinsmentioning
confidence: 99%
“…An in silico docking study demonstrated the potential of M pro , the main protease of SARS-CoV-2, to bind a range of statins, possibly Envelope cholesterol is crucial for IAV entry and fusion to host cell membrane 6 Dietary cholesterol increased IAV infection in mice 7 Treatment with cholesterol lowering drugs significantly decreased IAV propagation in human airway epithelial cells 8 Effect of statins Statins reduced COVID-19 fatalities and severity by 30% 9 Use of statins reduced mortality due to COVID-19 in a retrospective observational study 10 Statin treatment in hospitalised COVID-19 patients reduced death rates and complications including acute kidney infection, sepsis and acute respiratory distress syndrome 11 Statin treatment reduced deaths due to COVID-19 in hospitalized patients 12 Potential binding with main protease (M pro /NSP5), which is unique to and highly conserved in all coronaviruses 13 Rosuvastatin and atorvastatin reduced IAV proliferation in kidney cells 14 Atorvastatin reduced IAV infection of MDK cells by >95% 15 A UK study showed a slight but not significant protection against hospitalisation and death in statin users 16 Statin usage in hospitalised patients with influenza was associated with reduced death rates 17 A moderate dose statin administration reduced the risk of death due to influenza and chronic obstructive pulmonary disease (COPD) 18 explaining how statins can impede viral proliferation 13 Cys145 and His41 catalytic residues 24 . Our own in silico docking analysis of SARS-CoV-2 M pro with statins demonstrates possible binding at the active site (including binding with Cys145 and His41) of the protease (Figure 2).…”
Section: Sars-cov-2 Main Protease (M Pro )mentioning
confidence: 99%